2003
DOI: 10.1046/j.1468-1293.2003.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and outcome of hyperlactataemia in HIV‐infected patients*

Abstract: ObjectiveWe describe the prevalence, risk factors and outcome of hyperlactataemia (HL) in a cohort of 140 HIV-infected patients. Patients and methodsPatients were enrolled consecutively within a 3-month period (July to September 1999) and followed until 31 October 2000. One hundred and forty HIV-infected patients had venous plasma lactate levels measured. HL was de®ned at baseline by two consecutive lactate levels > 2.1 mmol/L (upper limit of normal). We compared baseline demographic characteristics, immuno-vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 17 publications
2
17
0
1
Order By: Relevance
“…Hyperlactatemia is a recognized consequence of mitochondrial dysfunction associated with d-drug use. 35 We found no association between African mtDNA haplogroups and hyperlactatemia, which is similar to the finding from another South African study. 36 There are inconsistent data regarding the influence of specific European mtDNA haplogroups on lipoatrophy.…”
supporting
confidence: 90%
“…Hyperlactatemia is a recognized consequence of mitochondrial dysfunction associated with d-drug use. 35 We found no association between African mtDNA haplogroups and hyperlactatemia, which is similar to the finding from another South African study. 36 There are inconsistent data regarding the influence of specific European mtDNA haplogroups on lipoatrophy.…”
supporting
confidence: 90%
“…2,7 The majority of cases appear to be associated with regimens containing didanosine and stavudine, but there have also been reports in association with zidovudine, and lamivudine. 1,11,15,16 Acidosis results most frequently when they are used in combination, but may also occur when only one of these medications is included in a therapeutic regime. This observation is supported by in vitro evidence that suggests additive or synergistic long-term mitochondrial toxicity in some NRTI combinations.…”
Section: Discussionmentioning
confidence: 99%
“…The associations between SHLA and exposure to d4T and ddI were initially described in a number of small crosssectional and cohort studies [10][11][12][13][14][15]. Recently, 110 cases of SHLA were pooled across multiple countries to conduct a case-control study, which identified advanced age, low nadir CD4 cell count, exposure to d4I and ddI and female gender as additional associations [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although hyperlactataemia and lactic acidosis have become rare in developed world settings, they are still considered significant challenges to large-scale ART provision in developing countries. A better understanding of the risk factors for SHLA is important in combating the morbidity and mortality associated with such an adverse event.Although the World Health Organization (WHO) now recommends tenofovir (TDF) or zidovudine (ZDV) as the preferred NRTIs for combination with lamivudine (3TC) or emtricitabine (FTC) in standard first-line regimens [8], d4T-based regimens continue to be widely used in developing countries, for reasons of cost, availability, and ease of administration [9].The associations between SHLA and exposure to d4T and ddI were initially described in a number of small crosssectional and cohort studies [10][11][12][13][14][15]. Recently, 110 cases of SHLA were pooled across multiple countries to conduct a case-control study, which identified advanced age, low nadir CD4 cell count, exposure to d4I and ddI and female gender as additional associations [16].…”
mentioning
confidence: 99%